Acrylic resins for manufacturing dental prosthetic restorations – microstructural, micromechanical and tribological tests - Bojko, Łukasz; Pałka, Paweł; Ryniewicz, Anna M.; Ryniewicz, Wojciech (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
When planning and manufacturing a removable dental prosthesis, efforts should be made to optimally distribute pressure without exceeding the threshold of the physiological capacity of tissues, especially since this type of restoration often causes prosthetic stomatopathies and atrophy of the bone substrate. The aim is to evaluate acrylic prosthetic structures in terms of microstructure, micromechanical parameters, resistance to movement in sliding friction, and wear resistance in the environment of physiological saline and artificial saliva. The research material includes removable prosthetic restorations made of acrylic resins manufactured in the Materials Science Laboratory at the Department of Dental Prosthetics of the Jagiellonian University Medical College. The clinical functionality of the restoration consists of adapting to individual biomechanical forces and creating the most favorable conditions for proper occlusion. Microstructure tests allowed the identification of the surface layer in wear defects and indicated the Vertex Rapid Simplified material as the least susceptible to internal defects and cracks, which may constitute potential places for the growth of fungi and bacteria. Micromechanical tests showed similar values of microhardness and longitudinal elastic moduli of the biomaterials tested. They may determine the strength and extent of the plate. Premacryl Plus had different and lower micromechanical parameters. Tribological tests facilitated a positive assessment of the effect of saliva on friction coefficients and forces. Reducing its value protects the tissues of the prosthetic base against the irritating effects of forces generated by the restoration under chewing and occlusion conditions.